Ответы
Ответ дал:
1
1)H2CO3=H(+)+HCO3(-)
2)HCO3=H(+)+CO3(2-)
1)Mg(OH)2=MgOH(+)+OH(-)
2)MgOH=Mg(2+)+OH(-)
1)H3PO4=H(+)+H2PO4(-)
2)H2PO4=H(+)+HPO4(2-)
3)HPO4=H(+)+PO4(-)
1)Ca(OH)2=CaOH(+)+OH(-)
2)CaOH=Ca(2-)+OH(-)
2)HCO3=H(+)+CO3(2-)
1)Mg(OH)2=MgOH(+)+OH(-)
2)MgOH=Mg(2+)+OH(-)
1)H3PO4=H(+)+H2PO4(-)
2)H2PO4=H(+)+HPO4(2-)
3)HPO4=H(+)+PO4(-)
1)Ca(OH)2=CaOH(+)+OH(-)
2)CaOH=Ca(2-)+OH(-)
diasabaidullin:
спасибо
Похожие вопросы
1 год назад
2 года назад
2 года назад
7 лет назад
7 лет назад
8 лет назад
8 лет назад